1995
DOI: 10.1007/bf00130799
|View full text |Cite
|
Sign up to set email alerts
|

A novel cyclomaltodextrin glucanotransferase from Bacillus firmus that degrades raw starch

Abstract: An alkalophilicBacilhuJirmus secreting the enzyme cyclomaltodextrin glucanotransferase was isolated from soil. The enzyme attacked raw starch to produce cyclodextrins. Maximum cyclodextrins were produced from tapioca starch followed by potato and corn starch. About 49 % of tapioca starch (at 10 and 50 g/l) was converted to cyclodextrins. The main reaction products were p and y-cyclodextrins with 40 % and 8 % yield respectively. On prolonged incubation small amount of cr-cyclodextrin was also produced. The rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 10 publications
(7 reference statements)
1
26
1
1
Order By: Relevance
“…In the presence of maltodextrin, the CD production was of three types, α-, β-, and γ-CD, while in soluble starch, there was production of only two types of CDs, β-and γ-CD, and no α-CD was observed. Many other CGTase studies have shown similar results, with the production of the β-CD prevailing (9,12,13,15,16,27,28,29). The better conversions were observed on 1.0% soluble starch, which showed a major conversion (80%) or in 2.5% maltodextrin (41%; Table 1).…”
Section: Effect Of Soluble Starch and Maltodextrin On CD Formationsupporting
confidence: 75%
See 2 more Smart Citations
“…In the presence of maltodextrin, the CD production was of three types, α-, β-, and γ-CD, while in soluble starch, there was production of only two types of CDs, β-and γ-CD, and no α-CD was observed. Many other CGTase studies have shown similar results, with the production of the β-CD prevailing (9,12,13,15,16,27,28,29). The better conversions were observed on 1.0% soluble starch, which showed a major conversion (80%) or in 2.5% maltodextrin (41%; Table 1).…”
Section: Effect Of Soluble Starch and Maltodextrin On CD Formationsupporting
confidence: 75%
“…9605 (10) were used. However, the CGTases from B. firmus (12,29,34) and B. clausii E16 produced only β-and γ-CD from different starches. The formation of only two types of CDs during hydrolysis processes is important in the separation process because it is easier to separate the CDs produced, which is interesting for industrial application.…”
Section: Effect Of Kind Of Starch On CD Formationmentioning
confidence: 97%
See 1 more Smart Citation
“…CGTase producers can be found in various places such as soil, waste, plantation, hot springs, and even deep-sea mud [ 11. Bacillus coagulans [2], Bacillus circulans [3], Bacillusfirmus [4], Bacillus stearothennophilus [5], Bacillus macerans Little information is available on the effects of fermentation conditions on CGTase production. Therefore, in this study, a preliminary screening process was carried out using Response Surface Methodology (RSM).…”
Section: * Author For Correspondence (R-rosli@utmmy)mentioning
confidence: 99%
“…Cyclodextrins (CDs), also known as Schardinger dextrins, are oligosaccharide rings comprising a-1, 4-linked glucopyranose residues. The most common types of CDs are a-, p-and y-cyclodextrins, which are made up of 6,7 or 8 molecules, respectively.…”
Section: Introductionmentioning
confidence: 99%